Influence of sulfur on the accumulation of mercury in rice plant (Oryza sativa L.) growing in mercury contaminated soils. (September 2017) - Li, Yunyun; Zhao, Jiating; Guo, Jingxia; Liu, Mengjiao; Xu, Qinlei; Li, Hong; Li, Yu-Feng; Zheng, Lei; Zhang, Zhiyong; Gao, Yuxi
Abstract: Sulfur (S) is an essential element for plant growth and its biogeochemical cycling is strongly linked to the species of heavy metals in soil. In this work, the effects of S (sulfate and elemental sulfur) treatment on the accumulation, distribution and chemical forms of Hg in rice growing in Hg contaminated soil were investigated. It was found that S could promote the formation of iron plaque on the root surface and decrease total mercury (T-Hg) and methylmercury (MeHg) accumulation in rice grains, straw, and roots. Hg in the root was dominated in the form of RS-Hg-SR. Sulfate treatment increased the percentage of RS-Hg-SR to T-Hg in the rice root and changed the Hg species in soil. The dominant Hg species (70%) in soil was organic substance bound fractions. Sulfur treatment decreased Hg motility in the rhizosphere soils by promoting the conversion of RS-Hg-SR to HgS. This study is significant since it suggests that low dose sulfur treatment in Hg-containing water irrigated soil can decrease both T-Hg and MeHg accumulation in rice via inactivating Hg in the soil and promoting the formation of iron plaque in rice root, which may reduce health risk for people consuming those crops. Highlights: Formation of iron plaque was promoted. Accumulation of Hg in rice was decreased. Mobility of Hg in the rhizosphere was reduced.